AN ANALYSIS OF STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT DURING ONLINE LEARNING - Endah Purwaningsih; Samsul Hadi; Dwi Rahayu (English Education Study Program STKIP PGRI Pacitan, 2022)
Online learning in the descriptive text is a challenge for the teacher and student. However, learning activities should be held to make students’ understanding of material well even the condition always different and need new adaptation. In reality, the learning model influences students’ ability, particularly in the learning of descriptive text. The research aims to analyze students’ cases based on the source of the problem in writing descriptive text. This research includes qualitative research, particularly case study research. The analysis uses Spradley Analysis which consists of domain analysis, taxonomy analysis, componential analysis, and theme cultural. In the domain, there are two domains such gender and distance between house and school. As a result of the research, students suffer high problems in four indicators. They consist of organization, grammar, mechanics, and word choice. In the gender category, female students have high cases. Besides, in the distance between school and house, the 6,1-10 KM students suffered the high problem. Further, it can conclude that students’ ability in writing descriptive text is low.